Construction of the green function of some differential equations with normal operator coefficients - Gadirli, N. A. (Національний технічний університет "Харківський політехнічний інститут", 2026)
The construction of the Green’s function for higher-order differential equations is considered in this work. The Green’s function of the operator defined by a differential equation and boundary conditions whose coefficients are specified at an arbitrary point taken from the half-axis is sought in the form.
Keywords: differential equations; operator coefficients; boundary conditions; operators